2018
DOI: 10.1002/eco.1944
|View full text |Cite
|
Sign up to set email alerts
|

Differential isotopic characteristics of eco‐hydrologic processes in a subtropical watershed, China

Abstract: In order to better understand isotopic characteristics of eco‐hydrologic processes in subtropical zones, this study selected a typical subtropical watershed in China to investigate and determine the complex differential mechanisms inherent to this water body type. Results showed that stable isotopes in precipitation within a Local Meteoric Water Line in the Xiangxi River basin (where δD = (8.23 ± 0.27)δ18O + (17.97 ± 1.65); R2 = 0.94) weighted δD and δ18O average precipitation values were −22.11‰ and −5.23‰, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 53 publications
1
2
0
Order By: Relevance
“…The δ 15 N source in baseflow mainly derived from soil erosion, local fertilizer application, livestock, plant litter, and deposition from industry, vehicle transportation, and agriculture, but ammonium fertilizers were a minor source of NO 3 − ‐N in the Xiangxi River watershed (Hao, Gao, et al, ), which was similar to results from other studies conducted around the Yellow River (Yue, Li, Liu, Zhao, & Ding, ). Our study also showed that the NO 3 − consumption rate that derived from denitrification was higher than the NO 3 − production rate derived from nitrification, which led to changes in δ 15 N enrichment in soil solutions (Cheng, Fang, Yu, Zhu, & Zheng, ; Fang et al, ; Yue, Li, CQi, Lang, & Ding, ).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The δ 15 N source in baseflow mainly derived from soil erosion, local fertilizer application, livestock, plant litter, and deposition from industry, vehicle transportation, and agriculture, but ammonium fertilizers were a minor source of NO 3 − ‐N in the Xiangxi River watershed (Hao, Gao, et al, ), which was similar to results from other studies conducted around the Yellow River (Yue, Li, Liu, Zhao, & Ding, ). Our study also showed that the NO 3 − consumption rate that derived from denitrification was higher than the NO 3 − production rate derived from nitrification, which led to changes in δ 15 N enrichment in soil solutions (Cheng, Fang, Yu, Zhu, & Zheng, ; Fang et al, ; Yue, Li, CQi, Lang, & Ding, ).…”
Section: Discussionsupporting
confidence: 84%
“…The dual isotopic approach also enables us to trace denitrification, because this process generates δ 18 O to δ 15 N between 0.5 and 1 values. Certain sampling points in the study area were between the 1:1 and 1:2 ratio, which means that denitrification occurred in certain sampling points in the Xiangxi River watershed (Hao, Gao, Sun, & Wen, ). The δ 15 N‐NO 3 and δ 18 O‐NO 3 showed seasonal changes can be explained by that nitrates would be enriched in 18 O during chemical reactions with tropospheric O 3 .…”
Section: Discussionmentioning
confidence: 99%
“…however, with n (A, B, C, …) isotope systems and >n+1 sources, we were still able to apply the requirement for mass balance conservation to determine multiple combinations of source proportions that offer feasible solutions (Phillips and Gregg, 2003;Hao et al, 2018).…”
Section: Discussionmentioning
confidence: 99%